Dienogest does not augment the gene expression of adhesion molecules, MCP-1, and monocyte adherence in human endothelial cells - Nanami Tahara; Fumitake Ito; Mari Kawamata; Masahiro Otani; Taisuke Mori (Taylor & Francis Group, 2023)
AbstractObjective Medroxyprogesterone acetate (MPA) may increase the risk of atherosclerosis during hormone replacement therapy (HRT); therefore, the effect of progestogens other than MPA on atherosclerotic lesions requires evaluation. Adhesion of monocytes to vascular endothelial cells is an important early step in atherosclerosis progression. MCP-1 is a key chemokine that promotes monocyte migration and adhesion to vascular endothelial cells. In this study, we investigated the effects of dienogest (DNG), an alternative progestogen, on monocyte adhesion and cytokine expression in human umbilical vein endothelial cells (HUVECs).Study Design HUVECs were treated with DNG, natural progesterone, or MPA, followed by interleukin (IL)-1β stimulation. The mRNA expression of adhesion molecules (E-selectin and ICAM-1) and cytokines (MCP-1 and IL-6) was examined using real-time PCR. A flow chamber system was used to examine the effect of DNG on the adhesion of U937 monocytic cells to monolayer HUVECs.Results Unlike MPA, DNG did not alter the mRNA expression of E-selectin, ICAM-1, MCP-1, and IL-6 in HUVECs. Moreover, it did not increase the number of monocytes adhering to HUVECs in the flow chamber system. However, MPA treatment significantly enhanced monocyte adhesion to HUVECs (p < 0.05).Conclusions DNG had no effect on the mRNA expression of adhesion molecules and cytokines in HUVECs, as well as the monocyte adhesion to HUVECs, suggesting that DNG can be explored as an alternative to MPA for HRT.